THE INFLUENCES OF LEADERSHIP, WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT YAMAHA MUSIK CIKARANG BRANCH - omah, enok (Universitas Mercu Buana, 2021)
Abstract: The declined phenomenon of employee performance that occurs at PT Yamaha Music Manufacturing Asia or commonly referred to as YMMA. This research aims to examine and analyze the effect of leadership and work environment on employee performance through job satisfaction as a mediating variable at PT YMMA. The research design that has been used is quantitative descriptive with 84 respondents. Data analysis using the Smart PLS application consisting of an outer model and inner model test. Based on results of processing and analysis data it was obtained that the leadership variable has a significant positive effect on job satisfaction, work environment variables have a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, the leadership variable has a positive and significant effect on employee performance, Work environment variables have a positive and significant effect on employee performance, leadership has an indirect effect on employee performance through job satisfaction and work environment variables have an indirect effect on employee performance through job satisfaction.